Factors influencing Malays as a second language learning in essay writing: a case study of Iban ethnic students in Sarawak, Malaysia - Edmund Austrus; Zamri Mahamod; Norhafizah Adnan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Second language learners, such as Iban students studying Malay, often face significant challenges in essay writing due to the proficiency gap between their first language and Malay. The lack of daily use of Malay further complicates their ability to grasp complex sentence structures and vocabulary, making essay writing a particularly difficult task for non-native speakers. This study aims to identify the factors influencing the learning of Malay as a second language in essay writing among Iban ethnic students. The study employed a qualitative research approach, involving semi-structured interviews with eight primary school Malay language teachers in the Kapit district of Sarawak. The data were analysed thematically using Nvivo 12 software. The findings identified three main factors: (i) mother tongue factors influence, (ii) linguistic environment factors influence, and (iii) psychological factors influence. As a result, the process of second language acquisition in educational settings requires deliberate and structured approaches, rather than relying on the natural language development seen with a first language. This study offers useful perspectives for both researchers and educators to refine teaching methods, focusing on more targeted strategies that can better support Iban students in improving their proficiency in Malay as a second language.